Are bronchodilator nebulizers superior to MDIs for the treatment of acute asthma exacerbations?. Issue 6 (June 2018) - Krylov, Vitaliy; Greuel, Jacob
Abstract : EVIDENCE‐BASED ANSWER : No. Bronchodilators delivered by metered‐dose inhaler (MDI) and spacer or nebulizer result in similar therapeutic benefits for adults and children with acute asthma exacerbation in the emergency department (ED). Children have fewer adverse effects and shorter ED stays with use of MDI and a spacer (SOR: A, meta‐analysis of RCTs). Furthermore, costs of the delivery system, medication, and personnel are lower for MDI and spacer therapy in adults (SOR: B, single small RCT).